The 100 most cited manuscripts in emergency abdominal surgery: A bibliometric analysis. (January 2017) - Ellul, Thomas; Bullock, Nicholas; Abdelrahman, Tarig; Powell, Arfon G.M.T.; Witherspoon, Jolene; Lewis, Wyn G.
Abstract: Background: The number of citations a scientific article receives provides a good indication of its impact within any given field. This bibliometric analysis aimed to identify the 100 most cited articles in Emergency Abdominal Surgery (EAS), to highlight key areas of interest and identify those that have most significantly shaped contemporary clinical practice in this newly evolving surgical specialty. This is of increasing relevance as concerns grow regarding the variable and suboptimal outcomes in Emergency General Surgery. Materials and methods: The Thomson Reuters Web of Science database was used to search using the terms [Emergency AND Abdom* AND Surg*] to identify all English language, full manuscripts. Results were ranked according to citation number. The top 100 articles were further analysed by subject, author, journal, year of publication, institution, and country of origin. Results: The median (range) citation number of the top 100 out of 7433 eligible papers was 131 (1569-97). The most cited paper (by Goldman et al., Massachusetts General Hospital, New England Journal of Medicine; 1569 citations) focused on cardiac risk stratification in non-cardiac surgery. The Journal of Trauma, Injury, Infection and Critical Care published the most papers and received most citations (n = 19; 2954 citations. The majority of papers were published by centres in the USA (n = 52; 9422 citations), followed by the UK (n = 13; 1816 citations). The most common topics of publication concerned abdominal aneurysm management (n = 26) and emergency gastrointestinal surgery (n = 26). Conclusion: Vascular surgery, risk assessment and gastrointestinal surgery were the areas of focus for 59% of the contemporary most cited emergency abdominal surgery manuscripts. By providing the most influential references this work serves as a guide to what makes a citable emergency surgery paper. Highlights: A Bibliometric analysis was performed, establishing the most influential publications in emergency abdominal surgery. Vascular surgery, risk assessment and gastrointestinal surgery are the topics most commonly cited. Emergency surgery for cancer and intra-abdominal sepsis are relatively poorly represented.